Degreening Characteristic of Musa AAA 'Berangan' and "William Cavendish' Bananas - Ding, Phebe (2004)
A study was conducted on the changes in cellular structure, physiology and physiochemical of Musa AAA 'Berangan' and 'Cavendish' as the ripening progressed at 18+2 and 2722 OC. Mature green (ripening stage (RS) 1) bananas were initiated to ripen using 0.02% acetylene from calcium carbide (CaC2) source (with an equivalent of 1 g cac2.kg-' fruit) for 24 h. A hand of Berangan and Cavendish fmit was split into 2 clusters. One of the clusters was initiated and ripened at 18t2 OC RH 90- 94%, while the other was initiated and ripened at 2722 OC RH 75-80%. The experiment was conducted using randomized complete block design with four replications. Five fruits per replicate were used. The various ripening stages were evaluated with the aid of FAMA visual colour score until the fruit turned intosdl? yellow at RS 6. For the Cavendish ripened at 27+2 OC (C27) where the fruit failed to degreen, the evaluation was done daily until senescence, when brown specks appeared on the peel. Data from measurements of ripening duration, L*, C* and h0 values, chlorophyll a, b and total chlorophylls, water loss, stomatal density, stomatal length and opening, peel thickness, peel and pulp fresh and dry weight, cell length and width of photosynthetic, epidermal, crystalliferous, tanniferous and starch granules, pulp firmness, soluble solids concentration (SSC), titratable acidity and pH were analysed using analysis of variance and differences between means were determined by Duncan Multiple Range Test. Data from starch iodine test, cellular structure and ultrastructure were documented as photographs or micrographs. Berangan degreened naturally under tropical ripening temperature of 27+2 OC, and a golden yellow fruit of RS 6 was obtained within 4 d of ripening. In contrast, Cavendish failed to degreen at 27+2 OC even though the pulp had softened. By day 5 after the acetylene treatment brown specks started to appear on the fruit surface indicating senescence had commenced. Cavendish could only degreen when ripened at 1822 OC, and a yellow fruit of RS 6 was obtained after 9 d of ripening. On the contrary, Berangan could not degreen and ripen under 1822 OC thus the fruit was discarded. TEM revealed that at RS 6 the grana-thylakoid membrane of chromoplast Berangan ripened at 2722 OC (B27) and Cavendish ripened at 1852 OC (C18) had lysed. Besides, plastoglobuli increased in number, and types of staining density and vesicles increased in number and size. However at day 5 of C27, the grana-thylakoid membrane retained and this was in concurrent with the high retention of chlorophyll content in fruit peel. The total chlorophyll retained in C27 was 57%, while only 25 and 40% of total chlorophyll was retained in B27 and C18 respectively. The high retention of chlorophyll content in C27 had caused it to correlate significantly with L*, C* and h0 values. Among B27, C18 and C27, C27 encountered the most water loss. However, there was no correlation between water loss and stomata1 density and opening. The existence of cracks and pores on the banana peel surface could be the iii passage for water loss. The severe water loss caused the peel thickness of C27 to be the thinnest among the bananas studied although initially its peel was thicker than B27. The fruit pulp and peel behaved differently towards ripening temperature. The moisture content in pulp increased, while no moisture content in peel decreased as ripening progressed. This led to increase of pulp to peel fresh weight ratio and C27 had the highest ratio as compared to C18 and B27. The softening of the banana fruit was due to starch degradation and dissolution of middle lamellae. SEM revealed that the pulp starch granules decreased in size and density as ripening progressed. The blue-black stained area of starch-iodine complex cleared from the central core of fmit towards the periphery of peel in all the bananas studied. The clearing pattern was most rapid in C27. The hydrolysed starch increased the SSC of all the bananas studied but the most significant increase was in C27. The titratable acidity of the three bananas studied increased then decreased as ripening progressed. In contrast, the pH decreased then increased as contrary to the trend of titratable acidity. The tropical temperature of 2722 OC, besides failing to degreen, had caused poor keeping and eating quality of Cavendish.